A pixel counting technique for sun patch assessment within building enclosures. (15th May 2019) - Rocha, Ana Paula de Almeida; Rodler, Auline; Oliveira, Ricardo C.L.F.; Virgone, Joseph; Mendes, Nathan
Highlights: Pixel counting technique for interior sunlit area calculation is experimentally validated. Simulation skillfulness for complex geometries of the pixel counting is investigated. Pixel counting has good agreement with the experiments. The impact of internal sun patch position on surface temperature is highlighted. Importance of computer graphic development to modernize solar energy assessment. Abstract: Pixel counting (PxC) emerged as a powerful technique for external solar shading calculations of buildings, providing accurate results with great computational efficiency even for dense geometries. Motivated by this fact and because the technique can be also adapted to cope with interior surfaces without further ado, this paper aims at experimentally evaluating the PxC technique implemented in Domus software for calculating sun patch distribution within building enclosures. For the validation purpose, digital images were taken from the surfaces of an experimental house to compare with the simulation results obtained by using EnergyPlus and two PxC based tools: Domus and Shading II SketchUp plug-in. This first task has shown that the PxC presents results in good agreement with the experimental data, in terms of both location and area of the sun patch. Also, a second case study was constructed to evaluate the capability of PxC for simulating non-convex zones with perforated shading elements. The results, in general, have shown that the PxC can provide accurate results in situations where polygon clipping based algorithms cannot be applied.